Americas : the changing face of Latin America and the Caribbean - Winn, Peter (Berkeley, Calif. : University of California Press, 2006)
The most authoritative history available of contemporary Latin America and the Caribbean. From Mexico to Tierra del Fuego, and from Cuba to Trinidad and Tobago, Americas examines the historical, demographic, political, social, cultural, religious, and economic trends in the region. For this new edition Peter Winn has provided a new preface and made revisions throughout to include the most up-to-date information on changes and developments in Latin America since the last revised edition of 1999.--From publisher description.
A view from the south -- Legacies of empire -- The perils of progress -- A second independence? -- Capital sins -- Continent on the move -- Children of the sun -- A question of color -- In women's hands -- The power and the glory -- The magical and the real -- Endangered states -- Making revolution -- North of the border.
Includes bibliographical references and index.
Keywords: Hispanic Americans -- History; Latin America -- History; Caribbean Area -- History